Catalog of Recent and fossil turrids (Mollusca: Gastropoda) - Tucker, John K. (Zootaxa, 2004)
More than 11,350 species group taxa have at one time or another been assigned to the Conoidean gastropod group commonly referred to as turrids. A catalog including Recent and fossil species belonging to the Drilliidae, Pseudomelatomidae, Strictispiridae, Turridae, and six of the seven subfamilies of the Conidae is presented. Species described in the Terebridae and the Coninae (sensu stricto) are excluded. The catalog is descriptive and no new generic assignments are made nor are new synonymies proposed. However, much of the secondary literature is also reviewed for each taxon, allowing previously proposed synonymies and generic assignments to be quickly found and evaluated. Preliminary analysis of the taxa included found temporal and geographical variation in the make up of Conoidean faunas. In general, Conidae (sensu stricto) have increased in importance, whereas Turridae have declined in importance from Cretaceous to Recent. In all extant faunas, Conidae (sensu stricto) dominate and range from 44.8% to 91.5% of the faunas from broadly defined geographic regions. Species diversity is high with more than 3000 Recent taxa potentially valid species. With a 38 species/year rate of species description, the number of valid Recent species could increase by one-third in the next 50 years. Because slightly more than one-half of the taxa are fossil species and description of new species is rapid among the fossils, known diversity is also increasing among fossil taxa. Unfortunately a large number of species-level taxa were found that are little known and need study to determine their place in turrid systematics. Regardless, the catalog provides a foundation for future studies of these important marine carnivorous gastropods.